Aspectos reprodutivos, morfologia dos gametas e desenvolvimento embrionário de Astyanax altiparanae Garutti & Britski (Teleostei, Characidae) - Santos, Matheus Pereira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to study basic aspects of gametes and early development of yellowtail tetra Astyanax altiparanae, for future application in biotechnology including chromosome and embryo manipulation. In Chapter I, the oocytes were analyzed by Scanning Electron Microscopy (SEM) and the insemination dose was determined. Semen was also collected and analyzed using a Computer Assisted Sperm Analysis (CASA). Such a reduced inseminating dose was explained by oocyte morphology because SEM analysis revealed villosities surrounding the micropyle that is related to the sperm guidance for fertilization. In addition, the duration of sperm motility was longer in comparison to most teleosts, what may improve fertilization ability. In Chapter II, several parameters related with fertilization were described, including the second polar body extrusion, fusion of the pronuclei and the formation of the fertilization cone. Moreover, the effect of three temperatures (22°C, 26°C and 30°C) on developmental stages was determined. 2nd polar body was extruded at 4-6 minutes post fertilization (mpf), and the pronuclei were formed at 8-10 mpf. The sperm showed a spherical head, midpiece and flagellum. As expected, higher temperatures gave rise to faster development and hatching. The information obtained in this study will open new possibilities in the field of chromosome and embryo manipulation including poliploidy, chimerism, transgenesis and other techniques

O objetivo deste trabalho foi estudar aspectos básicos dos gametas e o desenvolvimento inicial de Astyanax altiparanae, para futura aplicação na área de biotecnologia, incluindo manipulação cromossômica de embriões. No Capítulo I, os ovócitos foram analisados por Microscopia Eletrônica de Varredura (MEV) e a dose inseminante foi determinada. O sêmen também foi coletado e analisado com sistema de análise computadorizada (CASA). A dose inseminante reduzida encontrada para a espécie foi explicada pela morfologia dos ovócitos através de análise em MEV, que revelou vilosidades que cercam a micrópila relacionadas à orientação do esperma para a fecundação. No capítulo II, vários parâmetros relacionados com a fertilização foram descritos, incluindo a extrusão do segundo corpúsculo polar, a fusão dos pronúcleos e a formação do cone de fertilização. Além disso, o efeito de três temperaturas (22°C, 26°C e 30°C) sobre os estádios de desenvolvimento foi determinado. A extrusão do segundo corpúsculo polar ocorreu em 4-6 minutos pós-fertilização (mpf), e os pronúcleos fundiram-se com 8-10 mpf. O espermatozoide apresentou uma cabeça esférica, peça intermediária e flagelo. Como esperado, as temperaturas mais elevadas deram origem a um desenvolvimento e incubação mais rápidos. As informações obtidas neste estudo irão abrir novas possibilidades no campo da manipulação cromossômica de embriões, incluindo poliploidia, quimerismo, transgenia e outras técnicas
Keywords: Peixe - Reprodução; Astyanax (Peixe); Lambari (Peixe); Gameta; Morfologia (Animais); Embriologia; Fishes